China-Nigeria Infrastructural Development Strategies: An Assessment of the Investments of Chinese Companies and Implications for Nigeria’s Development Prospects - Esidene, Erunke Canice; Godiya , Atsiya Pius; Sadiq, Yahaya Abubakar (Kashere Journal of Politics and International Relations, 2023)
The core objective of this paper is to examine the nexus between investments of the Chinese companies and how that can enhance infrastructural development relations in view of the increasing role of Chinese companies’ investment trajectory. The study is particularly hinged on the examination of investment drive of the Peoples Republic of China in Nigeria and the extent to which some of these efforts could affect development in the country. Recent studies by experts have indicated increasing Chinese company’s investments by way of trade, finance, telecommunications, infrastructural development and expansion, among others. The fundamental question that has permeated scholarly debates for an umpteenth time is whether there is corresponding change and/or development in the nation’s economy or not. This study is an exploration of existing works of scholars in the broader discipline of China-Nigeria economic development interface. The study is a desk survey, and hence, employs vast majority of secondary sources as method of investigation. Essentially, the secondary sources include relevant existing research materials obtained from referred journals, monographs, books and archival sources. Findings have revealed that in spite of enormous Chinese companies’ investment in Nigeria, development has hardly improved. Further research investigations show that the nation’s internal contradictions orchestrated by corruption and high-scale complicity by the power elites have had stunting effects on development in Nigeria in virtually every facet of the nation’s landscape. The paper sums up with suggestions as panacea that could drive the anticipated developmental process of the Nigerian state in the 21st century and beyond.